Non-Assisted Hatching Trophectoderm Biopsy Does Not Increase The Risks of Most Adverse Maternal and Neonatal Outcome and May Be More Practical for Busy Clinics: Evidence From China - Li, Shuo; Ma, Shuiying; Zhao, Jialin; Hu, Jingmei; Li, Hongchang; Zhu, Yueting; Jiang, Wenjie; Cui, Linlin; Yan, Junhao; Chen, Zi-Jiang (Frontiers in Endocrinology, 2022)
OBJECTIVE To investigate whether the non-assisted hatching trophectoderm (TE) biopsy increases the risks of adverse perinatal outcomes in livebirths following elective single cryopreserved-thawed blastocyst transfer. PATIENTS AND METHOD(S) A total of 5,412 cycles from 4,908 women who achieved singleton livebirths between 2013 and 2019 were included in this retrospective cohort study. All embryos in this study were fertilized by intracytoplasmic sperm injection (ICSI) and cryopreserved through vitrification. Main intervention is to open the zona pellucida (ZP) of day 5/6 blastocyst immediately for biopsy without pre-assisted hatching. Main outcome measures are the common maternal and neonatal outcomes, including hypertensive disorders of pregnancy (HDPs), gestational diabetes (GDM), abnormal placentation, abnormalities in umbilical cord and amniotic fluid, preterm birth, cesarean section, low birth weight, postpartum hemorrhage, prolonged hospital stay (both mothers and infants). Generalized estimation equation (GEE) was used to control the effects of repeated measurements. Non-conditional logistic regression model was used to examine the associations between embryo biopsy status and each adverse perinatal event. Given the selection bias and changes in learning curve might affect results, we selected 1,086 similar (matching tolerance=0.01) cycles from ICSI group via propensity score matching (PSM) for second comparisons and adjustment (conditional logistic regression). RESULT(S) After adjusting for confounders, we confirmed the non-assisted hatching protocol did not increase the risks of most adverse maternal and neonatal outcomes. Despite this, there was an increased risks of GDM (aOR: 1.522, 95% CI: 1.141-2.031) and umbilical cord abnormalities (aOR: 11.539, 95% CI: 1.199-111.067) in the biopsy group. In the second comparisons after PSM, GDM incidence in the biopsy group was still higher (7.26% vs 5.16%, P=0.042), yet all measurement outcomes were equally likely to occur in both groups after the second adjustment. CONCLUSION(S) The non-assisted hatching TE biopsy does not increase the risks of most perinatal adverse outcomes. However, there is a higher GDM incidence in the biopsy group, and this association warrants further study. Considering its safety and simplicity, the non-assisted hatching protocol has the potential to become the preferred option for TE biopsy, especially in busy clinics and IVF laboratories.